Effects of cecropin antimicrobial peptides on growth and intestinal health in growing male minks - Chen, Jian; Yu, Xiaojun; Wang, Guang; Jiang, Ziyi; Kong, Lingpeng; Zhang, Huanle; Wang, Lihua (Frontiers in Veterinary Science, 2025)
This study investigated the effects of dietary supplementation with cecropin antimicrobial peptides (CAD) on growth performance and intestinal health in growing male minks (Neovison vison). A cohort of 60 male minks (65 days old) were evenly divided into six groups and fed a basal diet supplemented with CAD at 0 (control), 100, 200, 300, 400, or 500 mg/kg for 8 weeks. The findings revealed that the minks in 200 mg/kg CAD group had greater growth performance, with significantly higher final body weight (FBW) and average daily gain (ADG). Compared to the minks in the control (p < 0.05). Digestibility analyses at week 3 demonstrated that CAD supplementation enhanced ether extract (EE) digestibility (p < 0.05), while 200, 400, and 500 mg/kg CAD improved crude protein (CP) digestibility (p < 0.05). Intestinal morphology assessments indicated that 200 mg/kg CAD significantly increased duodenal and jejunal villus height (both p < 0.05) and jejunal villus height-to-crypt depth ratio (p < 0.05) compared to the control. Serum immunological analyses revealed elevated levels of complement C4 and IgG in CAD-supplemented groups (p < 0.05). Notably, the 100 mg/kg CAD group exhibited the higher serum IgA, IgM, and complement C3, and less jejunal TNF-α levels (all p < 0.05). Microbiota profiling showed that CAD supplementation reduced the relative abundance of Escherichia-Shigella and Mycoplasma, while 100, 200 and 400 mg/kg CAD decreased Peptostreptococcaceae populations (p < 0.05). The 100 mg/kg CAD group displayed optimal immune enhancement and microbiota modulation, whereas the 200 mg/kg group achieved the best growth performance and intestinal function. These results suggest that dietary CAD supplementation at 100–200 mg/kg effectively improves growth, nutrient utilization, and intestinal health in growing male minks.